Hydrothermal irreversibility analysis based on multi-criteria assessment in a modified spiral piping system utilized in solar ponds - Abu-Hamdeh, Nidal H.; Öztop, Hakan Fehmi; Alnefaie, Khalid A.; Wae-hayee, Makatar (Pergamon-Elsevier Science Ltd, 2020)
Present study provides a numerical simulation with experimental validation of the modified spiral piping system employed in solar ponds. The most important part of the solar ponds that plays a key role in its performance is its piping system, which has not been considered appropriately so far. To enrich this field, grooving the wall of the spiral piping system (which is considered to be placed at the lower convective zone (LCZ)) was adopted as an improvement mechanism. It is worth mentioning that in this innovative modification technique grooves were made in an annular form on the wall of spiral pipe with various spacing. Although made changes increases the extraction of heat from pond, it intensifies irreversibility to some extent. Therefore, various decisive parameters including distance between the grooves, depth of grooves, flow rate, fluid type, and inlet temperature (Pr) were considered to explore their contribution to entropy generation. Moreover, to find out which of Nu* (or Q) or S'(gen) outweighs the other one, the effect of said parameters analyzed based on the multi-criteria design concepts like h(W-S) and N-H. Three different working fluid including water, ethylene-glycol, and therminol-55 were used at different inlet tempera-tures (283K, 303 K, and 323 K) to cover a Pr range of 3.35-744. The obtained results show that with increment of flow rate and the depth of grooves also decreasing the pitch of grooves increases entropy generation. The maximum increment of N-H is about 26% when the depth of grooves is the highest and the pitch of grooves is the lowest. Results proved that, therminol-55 and ethylene-glycol are recommended when the inlet temperature goes up. The overall performance of solar pond is in a most desirable condition when eta(W-S) = 0.125. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: Irreversibility; Solar pond; Entropy generation; Spiral pipe